Marginal fit changes during porcelain firing cycles - (:unkn) unknown (My University, 1995)
The marginal fit changes that occur during the porcelain firing cycles of palladiumcopperand nickel-chromium copings both with shoulder and chamfer finish lines were investigated with scanning electron microscopy. Three copings from each alloy test group were used as nonporcelainized controls. Comparisons of the firing cycles revealed a greater change during the degassing stage, and the opaque firing caused a decrease in marginal gap. There was a small increase in gap size after firing body porcelain. The marginal fit change for the palladium-copper copings (19.39 μm) during degassing was significantly greater than that for the nickelchromium copings (8.65 μm). However, no significant differences were found when the effects of margin design and porcelain proximity to fit of metal-ceramic crowns were compared. © 1995 The Editorial Council of The Journal of Prosthetic Dentistry.